Navigating Challenges: Exploring Cadets' Perspectives on Maritime Cyber Resilience in STIP Jakarta's Semester 3 Program - Marudut Bernadtua Simanjuntak (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2023)
This qualitative study investigates the perspectives of 240 Semester 3 cadets at the Maritime Institute Jakarta (STIP Jakarta) regarding An Operational Approach to Maritime Cyber Resilience. Over three semesters, the research scrutinizes cadets' academic self-checked intelligence, perceived professional competences, motivations, and the interplay between language development and preparedness for global roles. The demographic diversity of the cadet sample, representing majors in Nautical, Technical, and Port and Shipping Management, ensures a comprehensive exploration of maritime education. The findings reveal a positive evolution in cadets' understanding of maritime cyber resilience, with a notable increase in academic self-checked intelligence. The curriculum's effectiveness in cultivating a nuanced comprehension of cyber threats is underscored by the enhanced professional competences perceived by cadets, indicating preparedness for the practical challenges in the maritime industry. Motivations and engagement exhibit a positive trajectory, from initial challenges to sustained interest, indicating the subject's growing relevance over time. The interconnected development of English language proficiency and subject mastery emphasizes the need for targeted language support within maritime education. The positive correlation between improved language fluency and a deeper understanding of maritime cyber resilience suggests the symbiotic relationship between linguistic and technical competence. The study's implications extend beyond STIP Jakarta, offering insights for refining maritime education globally. Recommendations encompass dynamic pedagogical approaches, continual curriculum evaluation, industry collaboration, and language enhancement initiatives. By embracing these recommendations, maritime education programmes can foster a resilient cadre of professionals adept at navigating the complexities of the modern maritime industry.